Pathogenesis-Related Gene Expression in Response to Trachyspermum ammi Supplementation Along With Probiotics in Chicken Salmonellosis and Insights in Drug Therapeutics - Haq, Zulfqarul; Ahmad, Syed Mudasir; Bashir, Ishrat; Dar, Mashooq Ahmad; Saleem, Afnan; Khan, Azmat Alam; Yatoo, Mohammad Iqbal; Mir, Shabir; Rastogi, Ankur; Hussain, Mohd Isfaqul; Shah, Riaz A.; Bhat, Basharat (Frontiers in Veterinary Science, 2022)
Salmonella enterica serovar typhimurium (S. typhimurium) is the leading cause of foodborne illness. Since Salmonella continues to have a detrimental effect on public health, there is an ongoing need to develop more advanced methods for combating Salmonellosis in foods before they reach consumers. In addition, the quest for alternative natural products has recently intensified due to increasingly stringent regulations regarding the use of antibiotics as growth promoters and consumer demand for antibiotic-free poultry products. This study evaluated the effect of Ajwain extract (AJE) on immune response and antioxidant status in broiler chicks challenged with Salmonella typhimurium. The chicks were infected with S. typhimurium and were divided into the different groups, except for the control group (CON). The challenged chicks received different treatments with 3 × 109 colony-forming unit (CFU) AciproTM-WS probiotic (PRO), 200 mg/kg Ajwain extract (AJE), 200 mg/100 kg of enrofloxacin (ENR), and a combination of 3 × 109 CFU AciproTM-WS probiotic and 200 mg/kg Ajwain extract (COM). Five days posttreatment, the tissue samples (liver and spleen) were analyzed. The results showed that basal diet supplemented with Ajwain extract (AJE) and a combination of probiotic and Ajwain extract (COM) significantly (P < 0.0.5) reduced the cytokine expression in broiler chicks challenged with S. typhimurium. Our findings suggest that AJE can clear the bacterial infection, improve antioxidant status, and suppress the inflammation response. Additionally, AJE supplementation significantly mitigated the S. typhimurium-induced increase in the interleukin-6 (IL-6) (liver and spleen), interleukin-8 (IL-8) (liver and spleen), interleukin-17A (IL-17A) (liver and spleen), and inducible nitric oxide (iNOS) (spleen and liver) levels (P < 0.05). We conclude that Ajwain is an efficient feed additive with antioxidant and anti-inflammatory properties. The interaction networks developed in this study provide a novel lead that could be targeted for anti-inflammatory and antioxidant properties.